Karakteristik Makro Algae Berzat Kapur di Perairan Tanjung Sira Lombok-Barat - Achmad Kadi (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Coastal waters of Tanjung Sira has calcareousalgae of the genus Halimeda limestone, Padina, Amphiroa, Galaxaura, Corallina, Hydrolithon, Mesophyllum, Peysonallia, Porolithon and Sporolithon. The substrate that used as habitat are sand, coarse sand, rocks and dead coral rubble. Calcium carbonate contained on calcareous algae fungsioning as adhesive and encrusting dead coral, shells of mollusks that have decayed and massive objects in the waters of the sea. The research aims was to determine the growth characteristics of calcareousalgae in the reef flats, local distribution, calcium carbonate contain and its contribution as a frame work coastal reef waters. The research method using transect (Buckland et al., 1993). Identification of the type of aragonite and calcite according to Cordero (1977). Analysis of calcium carbonate according to Hillis (1980). The results showed that the green and brown calcareousalgae found in the reef flats, has thallus and tubers. Red calcareousalgae grew as encrusting on dead reefs and massif substrate. There are 16 species of calcareous algae that found in reseach area, 10 species containing aragonite mineral and 6 species containing calcite mineral. The content of calcium carbonate on each species obtained 100-450 g/m² consists of aragonite and calcite minerals. Calcareousalgae contribute in the new formation of coral reef ecosystems. The other benefit of calcareaousalgae in the coastal waters is an additional food for herbivorous fish. The content of calcium carbonate on calcareousalgae species is used in pharmaceutical field as drug ingredients and supplements for humans.